Upaya Meningkatkan Pemahaman Guru dalam Implementasi Kurikulum Merdeka (IKM) Melalui Program Monitoring dan Evaluasi (Monev) Kegiatan In House Training (IHT) di SD Negeri Pedurungan Tengah 01 Kota Semarang - Rachmat Karno Utomo (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
This best practice activity is an activity that aims to increase teacher understanding in the Implementation of the Independent Curriculum (IKM). The main task of the teacher at school is to carry out the learning process in the classroom in accordance with the curriculum, in order to achieve these learning objectives optimally and with direction, teacher competency is needed in understanding a good learning curriculum and in accordance with the student learning environment. So that the learning tools they use become a teacher's need to develop a more meaningful learning process for students. The best practice results for this activity show that In House Training (IHT) can increase teachers' understanding of the Implementation of the Independent Curriculum (IKM) by implementing and developing learning tools that are in accordance with the real conditions in their respective classes.